Copper removal ability by Streptomyces strains with dissimilar growth patterns and endowed with cupric reductase activity - Albarracín, Virginia Helena (2008)
Morphological, physiological and molecular characterization of three copper-resistant actinobacterial strains (AB2A, AB3 and AB5A) isolated from copper-polluted sediments of a drainage channel showed that they belonged to the genus Streptomyces. These characteristics plus their distinctive copper resistance phenotypes revealed considerable divergence among the isolates. Highly dissimilar growth patterns and copper removal efficiency were observed for the selected Streptomyces strains grown on minimal medium (MM) added with 0.5 mM of copper sulfate (MMCu). Strain AB2A showed an early mechanism of copper uptake/retention (80% until day 3), followed by a drastic metal efflux process (days 5–7). In contrast, Streptomyces sp. AB3 and AB5A showed only copper retention phenotypes under the same culture conditions. Particularly, Streptomyces sp. AB5A showed a better efficiency in copper removal (94%), although a longer lag phase was observed for this microorganism grown for 7 days in MMCu. Cupric reductase activity was detected in both copper-adapted cells and nonadapted cells of all three strains but this activity was up to 100-fold higher in preadapted cells of Streptomyces sp. AB2A. To our knowledge, this is the first time that cupric reductase activity was demonstrated in Streptomyces strains.